Cell-free antigens from precocious Paracoccidioides brasiliensis culture induce a typical delayed-type hypersensitivity reaction - Fecchio, C. J. [UNESP]; Dias-Melicio, L. A. [UNESP]; Soares, A. M.V.C. [UNESP]; Guimarães, S. [UNESP]; Peraçoli, M. T.S. [UNESP]; Sartori, A. [UNESP] (FapUNIFESP (SciELO), 2011)
Cell-free antigens (CFAg) derived from Paracoccidioides brasiliensis have typically been used in immunodifusion reactions for serodiagnosis or therapeutic follow-up of paracoccidioidomycosis patients. Thus, we investigated the usefulness of CFAg obtained from cultures at diferent ages, to evaluate cellular immunity by the footpad test, in experimental murine paracoccidioidomycosis. Male mice infected with P. brasiliensis 265 strain were challenged in the footpad with CFAg obtained from four- (4d CFAg) or 11-day-old cultures (11d CFAg). The increase in footpad swelling provoked by 4d CFAg and 11d CFAg was similar and showed signifcant diference in relation to control groups. However, the infltrate pattern was strikingly diferent: 4d CFAg induced a predominant mononuclear infltrate whereas 11d CFAg provoked a predominant polymophonuclear infltrate. These diferent infammatory patterns were associated with distinct electrophoretic characteristics. By comparison with 11d CFAg, 4d CFAg showed more numerous and intense bands, including a strong one of 43 kDa (gp43). These results suggest that CFAg derived from Pb 265 isolate can be used as a reagent to evaluate cellular immunity; however, the culture's age is critical because only young cultures are able to induce a typical mononuclear infltrate. The efcacy of this new paracoccidioidin to assay the cellular immunity in infections caused by other P. brasiliensis isolates is under investigation.
Keywords: Cell-free antigens; Delayed-type hypersensitivity reaction; gp43; Murine paracoccidioidomycosis; Paracoccidioides brasiliensis